Impact-driven piezoelectric energy harvester using a pendulum structure for low-frequency vibration. (October 2021) - Fan, Guifen; Wang, Yanjiong; Tian, Feng; Hao, Mengmeng; Wen, Yue; Xu, Yanzhe; Zeng, FangFang; Lu, Wenzhong
This study investigates a pendulum ball impact-excited piezoelectric energy harvester (PEH) for low frequency vibration through finite element analysis and experimental verification. This structure can harvest the vibration energy of infrasonic level, which provides a new idea for the energy harvest of low frequency. Experimental results show that for a pendulum ball impact-excited PEH with a 2.5 mm horizontal displacement excitation at 2 Hz, namely the sinusoidal excitation acceleration of 0.04 g, the collision frequency between the pendulum and the cantilevers reaches 10 Hz, and the open-circuit peak voltage of two piezoelectric cantilevers in the collision is 30.1 and 27.1 V respectively. Under the parallel connection of two piezoelectric cantilevers, the open-circuit peak voltage is 15.8 V and a maximum output power of 10.53 μW can be achieved across a 130 kΩ external load resistance. Compared with a single pendulum ball structure, a bi-pendulum ball structure can interact with two cantilever beams in one collision, thereby improving the efficiency of energy collection and reducing the optimal load resistance. A maximum output power of 43 μW can be achieved across a 47 kΩ external load resistance and 2 Hz rotational vibration excitation.